2018
DOI: 10.3390/min8070305
|View full text |Cite
|
Sign up to set email alerts
|

What the Diffuse Layer (DL) Reveals in Non-Linear SFG Spectroscopy

Abstract: Following our recent work [Phys. Chem. Chem. Phys. 20:5190–99 (2018)] that provided the means to unambigously define and extract the three water regions at any charged interface (solid–liquid and air–liquid alike), denoted the BIL (Binding Interfacial Layer), DL (Diffuse Layer) and Bulk, and how to calculate their associated non-linear Sum Frequency Generation Spectroscopy (SFG) χ2(ω) spectroscopic contributions from Density Functional Theory (DFT)-based ab initio molecular dynamics simulations (DFT-MD/AIMD), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(83 citation statements)
references
References 33 publications
5
78
0
Order By: Relevance
“…Four independent simulations are performed, each separate trajectory starts from a random configuration of liquid water put in contact with the air, and the cation is added randomly at the interface. The electronic set-up follows our previous works [22,31] on air-water interfaces (neat and in presence of electrolytes). The simulations have been performed with the CP2K package [45,46], the BLYP [47,48] functional is adopted in combination with mixed Gaussian-Plane Waves basis sets and GTH pseudopotentials [49].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four independent simulations are performed, each separate trajectory starts from a random configuration of liquid water put in contact with the air, and the cation is added randomly at the interface. The electronic set-up follows our previous works [22,31] on air-water interfaces (neat and in presence of electrolytes). The simulations have been performed with the CP2K package [45,46], the BLYP [47,48] functional is adopted in combination with mixed Gaussian-Plane Waves basis sets and GTH pseudopotentials [49].…”
Section: Methodsmentioning
confidence: 99%
“…Once the interface is charged, the interpretation of the SFG signal starts to be more tricky as this spectroscopy now probes an interfacial region of far larger thickness than the BIL discussed above, [20,21,[28][29][30][31] where the final SFG signal is now a convolution of second (χ 2 (ω)) and third order (χ 3 (ω)) non-linear contributions, plus interferences [20,21,[28][29][30][31]. Tian et al have shown that any charged interface is composed of two distinct interfacial regions that are SFG active [20]: the Binding Interfacial Layer (BIL), i.e., the first water monolayer as shown in our recent works [21,31] (which is the only layer probed at neutral interfaces), and the Diffuse Layer (DL) made of the subsequent bulk water layer(s) reoriented by the surface field (at charged interfaces). The DL is made SFG active because the surface field induced liquid water reorientation breaks the liquid centrosymmetry.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations